How the infrared radiation affects the film formation process from latexes? - Yargi, O.; Gelir, A.; Ozdogan, M.; Nuhoglu, C.; Elaissari, A. (WILEY-BLACKWELL, 2016)
In this study, the effect of the infrared radiative heating (IRH) was investigated on the film formation from composites of polystyrene (PS) latex particles and poly vinyl alcohol (PVA). The films were prepared as a pure PS and a mixture of PS and PVA particles at equal compositions at room temperature and they were annealed at elevated temperatures above the glass transition temperature (T-g) of PS for 10 min by using IRH technique. Identical experiments were performed by using standard convectional heating technique in oven as comparison. It was shown that the activation energy for the film formation from PS latex particles decreased considerably in IRH annealing technique. Photon transmission (PT) and steady state fluorescence (SSF) techniques were used to monitor the film formation process at each sintering step. Minimum film formation temperature, T-o, and healing temperature, T-h, were determined by the data obtained from the SSF and the PT measurements for each heating processes. The film formation was modeled as a void closure and as an interdiffusion stage below and above T-h, respectively. Scanning electron microscopy (SEM) was used to examine the variation in morphological structure of annealed composite films. It was observed that IRH heating causes more homogenous and more flat film surface than films annealed in the oven. (c) 2015 Wiley Periodicals, Inc.
Keywords: films; glass transition; polystyrene; spectroscopy; THERMALLY-EXPANDABLE MICROSPHERES; PHOTON TRANSMISSION; MOLECULAR-WEIGHT; PARTICLES; INTERDIFFUSION; TEMPERATURE; ADHESION; Polymer Science